Recurrent Tissue-Specific mtDNA Mutations Are Common in Humans - Samuels, David C.; Li, Chun; Li, Bingshan; Song, Zhuo; Torstenson, Eric; Boyd Clay, Hayley; Rokas, Antonis; Thornton-Wells, Tricia A.; Moore, Jason H.; Hughes, Tia M.; Hoffman, Robert D.; Haines, Jonathan L.; et al. (PLoS genetics, 2013)
Mitochondrial DNA (mtDNA) variation can affect phenotypic variation; therefore, knowing its distribution within and among individuals is of importance to understanding many human diseases. Intra-individual mtDNA variation (heteroplasmy) has been generally assumed to be random. We used massively parallel sequencing to assess heteroplasmy across ten tissues and demonstrate that in unrelated individuals there are tissue-specific, recurrent mutations. Certain tissues, notably kidney, liver and skeletal muscle, displayed the identical recurrent mutations that were undetectable in other tissues in the same individuals. Using RFLP analyses we validated one of the tissue-specific mutations in the two sequenced individuals and replicated the patterns in two additional individuals. These recurrent mutations all occur within or in very close proximity to sites that regulate mtDNA replication, strongly implying that these variations alter the replication dynamics of the mutated mtDNA genome. These recurrent variants are all independent of each other and do not occur in the mtDNA coding regions. The most parsimonious explanation of the data is that these frequently repeated mutations experience tissue-specific positive selection, probably through replication advantage.